Alih dan Campur Kode Arab-Indonesia: Studi Sosiolinguistik di Pesantren MIMLAM Cileunyi - Azhar, Ruly Syaepul; Almaghfur, Ahmad Kholil; Nandang, Ade; Nasaruddin, Nur Sakinah Ahmad (Yayasan Cendekia Gagayunan Indonesia, 2025)
The phenomenon of code-switching and code-mixing is a linguistic dynamic that is prevalent in bilingual environments, including Islamic boarding schools. This research focuses on the practice of code transfer and Arabic-Indonesian code mixing used by students of the MIMLAM Cileunyi Islamic Boarding School in formal and informal interactions. The purpose of this study is to describe the types and forms of code switching and code mixing that appear, as well as analyze the factors behind it. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, semi-structured interviews, and documentation. The data were analyzed with the Miles and Huberman interactive model. The results of the study show that there are three main forms of code mixing, namely insertion, substitution, and congruent lexicalization, as well as several forms of intra-sentential code switching. This phenomenon is not only influenced by the limitations of language competence, but also functions as a communicative strategy and marker of social identity in the pesantren environment. The conclusion of the study emphasizes that code switching and code mixing can make a positive contribution to contextual Arabic learning and in accordance with the communication needs of students.